Personality of Sara Fitzgerald in My Sister Keeper Movie Directed by Nick Cassavetes (2009) : A Psychoanalytic Approach - NURCAYANTO., DARMAWAN (2012)
This study investigates personality of Sara Fitzgerald reflected in My Sister's Keeper movie viewed from psychological approach. This research is aimed to analyze personality of Sara Fitzgerald viewed in character of Sara based on psychoanalytic perspective and analyze the movie based on its structural elements. In achieving the objectives, the researcher uses descriptive qualitative method as the type of the research. The object of this study is My Sister's Keeper movie by Nick Cassavetes. The data sources are the primary data and secondary data. The primary data are the movie itself and the secondary data are the other data which have relationship with the study, such as some biography of the author, the books and other relevant information. In collecting the data, the researcher uses documentation method and the technique of the data analysis is descriptive analysis. Based on the psychoanalytic analysis, in My Sister's Keeper, Nick Cassavetes describes how the personality of Sara as one of causes the story which becomes interesting, because she has an interesting personality. She is a kind of mother who can give influence for the watcher because Sara gives example of a love of mother to family although in showing her love, she sometimes does not care with argument of other family member. The personality structures of Sara are id, ego, and superego, can be concluded id, ego, and superego which are important rules in building the character of Sara.